Peningkatan Hasil Belajar Kimia Siswa pada Pokok Bahasan Sistem Koloid Menggunakan Buku Ajar Kimia Inovatifproject Based Learning (PJBL) - Leny Novita; Kasrawati Kasrawati (JOURNAL OF INDUSTRIAL AND MANUFACTURE ENGINEERING, 2019)
The development of paradigm for the human resources potential needed indemandsin all areas, notjustthe qualityof human resources, buthumancharacteritself. Teaching innovations incorporated into textbooks is expected to enhance thequality of education and develop the character building ofthe nation's generation. This research aims to know learners gain optimal learning results. The population is allhigh schools inNorth Sumatra. The sampleinthis study were used research and development methodand taken by purposive sampling, namely SMA Hang Tuah Belawan, SMAN 9 Medan and SMAN 19 Medan each as much as 2classes. Experiment and Control Class. Data were analyzed by using independent sample t-test with SPSS 20 for windowsat significance level 0.05. Results showed that innovative chemistry textbook has been successfully improved the student learning out comes. Innovative textbook can be used to transform the original teacher centered learning into a student centered learning.